Gender and the Genocide in Rwanda Women as Rescuers and Perpetrators - Brown, Sara E. (2017)
This book examines the mobilization, role, and trajectory of women rescuers and perpetrators during the 1994 genocide in Rwanda. While much has been written about the victimization of women during the 1994 genocide in Rwanda, very little has been said about women who rescued targeted victims or perpetrated crimes against humanity. This book explores and analyzes the role played by women who exercised agency as rescuers and as perpetrators during the genocide in Rwanda. As women, they took actions and decisions within the context of a deeply entrenched patriarchal system that limited their choices. This work examines two diverging paths of women's agency during this period: to rescue from genocide or to perpetrate genocide. It seeks to answer three questions: First, how were certain Rwandan women mobilized to participate in genocide, and by whom? Second, what were the specific actions of women during this period of violence and upheaval? Finally, what were the trajectories of women rescuers and perpetrators after the genocide? Comparing and contrasting how women rescuers and perpetrators were mobilized, the actions they undertook, and their post-genocide trajectories, and concluding with a broader discussion of the long-term impact of ignoring these women, this book develops a more nuanced and holistic view of women's agency and the genocide in Rwanda. This book will be of much interest to students of gender studies, genocide studies, African politics and critical security studies.